Role of Tim-3 in Decidual Macrophage Functional Polarization During Abnormal Pregnancy With Toxoplasma gondii Infection - Zhang, Dan; Ren, Liqin; Zhao, Mingdong; Yang, Chunyan; Liu, Xianbing; Zhang, Haixia; Jiang, Yuzhu; Sun, Xinyue; Li, Teng; Cui, Lijun; Hu, Xuemei (Frontiers in Immunology, 2019)
Vertical transmission of the intracellular parasite Toxoplasma gondii (T. gondii) can lead to devastating consequences during gestation. Tim-3, a negative immune regulator, is constitutively expressed on decidual macrophages, but its specific role during T. gondii infection has not yet been explored. In the present study, we discovered that Tim-3 plays an important role in the abnormal pregnancy due to T. gondii infection using Tim-3-/- pregnant mice and anti-Tim-3 neutralizing antibody treated human decidual macrophages. The results showed that abnormal pregnancy outcomes were more prevalent in Tim-3-/- infected pregnant mice than in wild-type infected pregnant mice. Tim-3 expression in decidual macrophages was significantly down-regulated after T. gondii infection both in vitro and in vivo. Tim-3 down-regulation by T.gondii infection could strengthen M1 activation and weaken M2 tolerance by changing the M1 and M2 membrane molecule expression, arginine metabolic enzymes synthesis, and cytokine secretion profiles of decidual macrophages. Moreover, Tim-3 down-regulation by T.gondii infection led to PI3K-AKT phosphorylation inhibition, downstream transcription factor C/EBPβ expression, and SOCS1 activation, which resulted in enzymes synthesis regulation and cytokines secretion. Our study demonstrates that Tim-3 plays an indispensable role in the adverse pregnancy outcomes caused by T. gondii infection.